Analysis of gut microbiota in patients with epilepsy treated with valproate: Results from a three months observational prospective cohort study. (January 2022) - Gong, Xue; Liu, Yue; Liu, Xu; Li, Ai Qing; Guo, Kun Dian; Zhou, Dong; Hong, Zhen
Abstract: Background: Growing evidence implicates the potential effect of microbiota on the pathogenesis and course of epilepsy. However, the effects of valproate (VPA), a broad spectrum anti-epileptic drugs, on gut microbiota have not been investigated in humans. This study aimed to analyze fecal microbiota in patients with epilepsy treated with valproate. Methods: A total of 10 participants, who were newly diagnosed of cryptogenic epilepsy with treatment naïve and received 1000 mg daily doses of VPA, were recruited in our prospective study. Microbiota compositions were evaluated at baseline and after three months of VPA treatment using 16S rDNA sequencing. Results: VPA treatment was associated with clinical improvements in all patients, but not changes in gut microbiota richness and complexity (Shannon: p = 0.82). Microbiome composition structure differences also revealed no statistical difference in dissimilarity (Adonis: p = 0.90). No statistical difference taxa were found between two groups. However, the ratio of phyla Firmicutes to Bacteriodetes (ANOVA: p = 0.037) markedly raised after three months of VPA-treatment. A correlation matrix based on the spearman correlation distance confirmed associations between specific fecal taxa and VPA-related clinical metabolic parameters, including drug concentration in the blood, total cholesterol, triglyceride, lactate dehydrogenase, alanine aminotransferase, aspartate aminotransferase and weight gain. ( p < 0.05) Conclusions: Among those patients treated with VPA, characterization of the gut microbiota altered, and gut microbiota associated with weight gain and clinical biochemical indexes, suggesting that microbiome composition data might involve in the mechanisms of VPA induced metabolic disorder. Highlights: Among patients treated with VPA, characterization of the gut microbiota not significantly altered. The ratio of phyla Firmicutes to Bacteriodetes markedly raised after three months of VPA-treatment. Microbiome composition data might involve in the mechanisms of VPA induced metabolic disorder.